Continuous Fermentation Coupled with Online Gas Stripping for Effective Biobutanol Production - Zhangnan Lin; Hongjuan Liu; Wei Cong; Jian’an Zhang (Fermentation, 2023)
The main problems with the butanol fermentation process include high cost of grain raw materials, low product concentration and low butanol productivity caused by butanol cytotoxicity. In this study, cassava, a cheap crop, was used as the raw material. A symbiotic system TSH06, which possesses the capability to synthesize butanol under non-strict anaerobic conditions, was used as the fermentation strain. The fermentation performance of TSH06 in a cassava system was investigated. In order to eliminate product inhibition and promote the concentration and productivity of butanol, a strategy of continuous fermentation coupled with online gas stripping was developed. By using the strategy of two-stage continuous fermentation using immobilized cells coupled with online gas stripping, the butanol productivity reached 0.9 g/(L·h); at the same time, a high butanol concentration was achieved, and the concentration of butanol obtained in the condensate reached 71.2 g/L.